Proyecto de comercialización de helados de yogurt en la ciudad de Guayaquil - Demanda, Rentabilidad (2009)
The market of desserts in the city of Guayaquil currently owns an unmet necessity, respect to characteristics and beneficial attributes for the health, every day the people taste diversity of desserts that are not natural and healthy. Frozen Yogurt's marketing in the city of Guayaquil is an alternative of dessert light to satisfy the above mentioned need, besides is based on the demand of consumers who are looking for a dessert Light that it allows them be seen and to feel well. The resource investment kicking off the first phase of the project are accessible; there is a space of 6 m2 located in Sun´s Mall, the infrastructure and 50 % of the capital to invest. This investment project shows there is an available market and resources necessary to carry out the same, searching make use of the characteristics and beneficial attributes for the health that the product will offer besides founding high quality services, therefore to get the loyalty of the same and to develop the brand.